3 - Household welfare perspective of family planning utilization in Uganda - Phionah Namuliira,; Razack B. Lokina,; Innocent Pantaleo, (African Sociological Review, 2022)
The rationale for FP use has changed over time to progressively emphasize poverty reduction and welfare improvements. However, literature hasn’t largely matched this change. This study, therefore, sought to contribute to this knowledge gap by exploring the impact of FP on household welfare using consumption per adult equivalent as the measure of household welfare. Data from the Uganda National Panel Survey 2018/19 and 2019/20 waves was used, and the analysis was done using pooled ordinary least squares. Results revealed that fewer male headed households and more of the women not using FP were poor as compared to their counterparts. Results also indicated FP use to increase household welfare by 6.4% among all households. This increase is however more significant for rural women. The results thus indicate the potential of using FP to bridge the rural-urban divide.